Breed choice and trypanosomosis risk - Gbodjo Zakpa, L.; D'Ieteren, G.D.M.; Diedhiou, M.; Leak, S.G.A.; Coulibaly, L. (European Union, 2001)
Decreasing efficacy of the trypanocidal drugs and difficulties of sustaining tsetse fly control, strengthen the importance of trypanotolerant livestock and the enhancement of disease resistance as options for livestock production. Continued increase in urban demand for meat and milk in West Africa, recent expansion of the demand for locally produced commodities, and increase demand of draught oxen are influencing breed choices towards increased size and milk production. In order to assess the influence of these conflicting trends on farmers decisions, studies of changes in breed compositions and farmers priority traits for breeding decisions were undertaken in mid-West Africa.